Pengaruh Beberapa Pupuk Organik Cair Terhadap Pertumbuhan Bibit Anggrek Vanda Sp - Prihartomo, Dwi; listiawati, Agustina; diyani, Rahmi (Jurnal Sains Mahasiswa Pertanian, 2018)
Orchid Vanda sp is one of the most popular orchids. The number of request for the Vanda sp orchid must be balanced with sufficient seed production. Seedling of orchids in pots will grow well if it has suitable planting media, good treatment and fertilization. One of the alternatives that must be done to fulfill the nutrient needs of orchid seeds isÂ  fertilization. The aim of this research is to get the best liquid organic fertilizer on the growth of Vanda sp. This research was conducted in experimental garden at Agriculture faculty of Tanjungpura University Pontianak. This study used the Completely Randomized Design (RAL) experimental method, which consisting of 5 treatment levels and each treatment consisting of 5 replications and each treatment unit consisting of 4 plants. A total of 100 plants were obtained. The treatment that we used was Liquid Organic Fertilizer ,which were A: Pupuk Sugih, B: Top G2 Fertilizer, C: Green Tonic Fertilizer, D: Super NPK Indovit Fertilizer, E: NPK Plus Natural TE fertilizer. The variables observed in this study were the increase of leaf length (cm), the increase of leaf number (strands), the increase of leaf width (cm) and the increase of the number of roots (strands). Based on the result of the research, it can be concluded that the best liquid organic fertilizer is not found, but Green Tonic and NPK Plus TE natural fertilizer can be used as fertilizer for leaf growth, and the number of leaves, orchid vanda sp.Â Keywords: Orchid Seeds Vanda sp, Liquid Organic Fertilizer, Type of Fertilizer